Vitamin D Status and Supplementation in Adult Patients Receiving Extracorporeal Membrane Oxygenation. Issue 6 (November 2018) - Nair, P.; Venkatesh, B.; Hoechter, D. J.; Buscher, H.; Kerr, S.; Center, J. R.; Myburgh, J. A.
The prevalence of vitamin D deficiency in critical illness is known to be high and associated with adverse clinical outcomes. Patients receiving extracorporeal membrane oxygenation (ECMO) may be at increased risk of vitamin D deficiency due to high severity of acute illness. Challenges with drug dosing in ECMO patients are recognised due to increased volume of distribution and drug absorption to circuit components. To describe the prevalence of vitamin D deficiency in ECMO patients and the effect of intramuscular dosing of cholecalciferol on levels of vitamin D metabolites, and to compare these data with intensive care unit (ICU) patients not receiving ECMO, two prospective studies were performed sequentially: an observational study of 100 consecutive ICU patients and an interventional study assessing effects of intramuscular cholecalciferol in 50 ICU patients. The subgroup of patients who required ECMO support in each of these studies was analysed and compared to patients who did not receive ECMO. Twenty-four ECMO patients, 12 from the observational study and 12 from the interventional study (who received intramuscular cholecalciferol) were studied—21/24 (88%) ECMO patients were vitamin D deficient at baseline compared to 65/126 (52%) of non-ECMO patients (P=0.006). Of the 12 ECMO patients who received cholecalciferol, six patients (50%) achieved correction of deficiency compared to 36/38 (95%) non-ECMO patients (P=0.001). The prevalence of vitamin D deficiency is higher in ECMO patients compared to other critically ill adults. Correction of deficiency with single dose cholecalciferol is not reliable; higher or repeated doses should be considered to correct deficiency.